The Influence of Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) on Profitability (Survey on Foreign Exchange Commercial Banks Listed in Indonesia Stock Exchange the Year 2011-2015) - Surtikanti Surtikanti; Asep Saepudin; Yashinta Arizona; Sri Dewi Anggadini (Indonesian Journal of Economics, Social, and Humanities, 2022)
The study empirically partially the influence of Capital Adequacy Ratio and Net Interest Margin to Profitability (Return On Asset) in listed Foreign Exchange Commercial Banks in Indonesia Stock Exchange from 2011 to 2015. Problems that occur in Foreign Exchange Commercial Banks is the increase Capital Adequacy Ratio and Net Interest Margin but not followed by a rise of the return on assets. The research uses descriptive analysis verification in 24 Foreign Exchange Commercial Banks of sample select by using purposive sampling, so obtained samples 8 Foreign Exchange Commercial Banks with 40 financial reports on listed Foreign Exchange Commercial Banks in Indonesia Stock Exchange from 2011 to 2015. Data analysis technique used is multiple linier regression analysis. These results indicate that the variabel of Capital Adequacy Ratio significantly influence the Profitability (Return On Asset) while Net Interest Margin variabel significantly influence Profitability (Return On Asset) on listed Foreign Exchange Commercial Banks in Indonesia Stock Exchange from 2011 to 2015.